2020
DOI: 10.34031/2618-7183-2018-1-2-30-36
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Receptural-Technological Parameters of Manufacture of Cellular Concrete Mixture

Abstract: aerated concrete at the moment is one of the perspective thermal insulation materials. However, the production of high-quality aerated concrete products is associated with a number of difficulties, primarily related to the features of the manufacturing technology and, in particular, to the formation of its structure during the period of gas evolution and the impact on this process of a large number of factors. The best conditions for the formation of cellular concrete are created when the maximum gas release a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
0
8
0
3
Order By: Relevance
“…Введение. Одним из наиболее актуальных вопросов в области ячеистых бетонов является повышение их эффективных свойств, в том числе с применением местного регионального сырья [1][2][3][4][5][6][7][8]. Российский и зарубежный опыт показывает, что наиболее перспективным и широко применяемым методом улучшения характеристик пенобетонов является микроармирование дисперсными волокнами [9][10][11][12][13].…”
Section: влияние микроармирования хризотил-асбестом разных марок на свойства и структуру пенunclassified
“…Введение. Одним из наиболее актуальных вопросов в области ячеистых бетонов является повышение их эффективных свойств, в том числе с применением местного регионального сырья [1][2][3][4][5][6][7][8]. Российский и зарубежный опыт показывает, что наиболее перспективным и широко применяемым методом улучшения характеристик пенобетонов является микроармирование дисперсными волокнами [9][10][11][12][13].…”
Section: влияние микроармирования хризотил-асбестом разных марок на свойства и структуру пенunclassified
“…For two millennia, a path has been forged from philosophy and the fundamental sciences to applied research; society has passed from the Stone Age to industrial and postindustrial and the nature of human consumption has radically changed [15][16][17][18]. However, by the beginning of the XXI century serious problems arose, without the solutions of which it is difficult to count on long-term progress in the development of society (Figure 1) [19][20][21][22][23][24]. Further development has been hampered by a lack of energy resources, environmental pressure on the human environment, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed the important role of the particle size distribution, the properties surface nature and specific surface in the raw mix for regulating the physical and mechanical building materials characteristics [1][2][3][4][5]. The main criterion is the natural and man-made raw materials genetic characteristics influence [6][7][8].…”
Section: Introductionmentioning
confidence: 99%